Cardiovascular risk and physical fitness analysis in mexican Urban Search and Rescue (USAR) firefighters - Espinoza-Gutiérrez, Roberto (2026)
Introduction: Firefighting imposes extreme physical demands on firefighters, increasing the risk of cardiovascular disease, especially in those who are overweight or obese. Objectives: To analyze the prevalence of cardiovascular risk factors related to body composition and physical fitness parameters in Mexican firefighters with USAR certification, as well as to examine the relationship between abdominal obesity, physical fitness parameters and blood pressure, and compare them with international populations. Methods: A descriptive, correlational, and cross-sectional study involving 49 firefighters (44 men and 5 women), with an average age of 38.1 ± 8.5 years. Grip strength, abdominal strength, and flexibility were assessed, and body composition was measured using the InBody 770 electrical bioimpedance test. Descriptive analyses and multivariate regression were used to evaluate the relationships between cardiovascular risk factors and physical fitness. Results: A significant association was found between abdominal obesity and systolic blood pressure (p < 0.01), as well as between abdominal obesity and abdominal strength (p < 0.05). Participants had a higher prevalence of overweight and obesity, a larger waist circumference, a higher percentage of body fat, and lower muscle mass, as well as lower physical performance than firefighters studied in other countries. Conclusion: Firefighters face risk factors that affect their cardiovascular health and occupational performance, with lower levels of physical fitness than firefighters in other countries.